The Implementation of Small Group Discussion Technique in Teaching Speaking Skill - Tania Yosvi Tamara Sinaga; Maya Oktora (Universitas Negeri Medan, 2025)
This research aimed to analyze the implementation of the small group discussion technique in teaching speaking skills to eleventh-grade students at SMA Negeri 2 Tebing Tinggi and to find out the challenges of implementing small group discussion techniques in the classroom. The research was conducted using a descriptive qualitative method that involved the English teacher. The teacher implemented this technique in two meetings. In the first meeting, the teacher divided the students into several groups and gave them time to discuss the topic that had been determined. In the second meeting, each group presented the results of their discussion in front of the class. During the implementation process, the teacher faced three main challenges: time management, classroom management, and student participation. However, although the teacher faced these challenges, the learning process went very well. This showed that the small group discussion technique could be an effective and enjoyable way to improve students’ speaking skills